2000
DOI: 10.1111/j.1708-8208.2000.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Brånemark System® Wide Platform Implants for Single Molar Replacement: Clinical Evaluation of Prospective and Retrospective Materials

Abstract: The study indicated that it was important to carefully perform surgery in posterior mandibles in order to preserve and optimally use the existing dense bone. It was suggested that from bone healing and remodeling aspects, posterior mandibles may be more demanding to handle than corresponding areas of maxillae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
2
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 8 publications
4
53
2
2
Order By: Relevance
“…Several authors have claimed that implants with wider diameters improve the bone-implant contact within compact bones and thus are preferable. [22][23][24] A study by Bischof et al 25 investigated ITI implants and found that a higher ISQ was seen in the maxilla than in the mandible and in type I than in type III bone; however, stability was not significantly related to site of placement or implant length and diameter. Additionally, up to 4 to 6 weeks after placement, ISQ was maintained or slightly increased, and after 6 weeks, the range of increment became larger.…”
Section: Discussionmentioning
confidence: 96%
“…Several authors have claimed that implants with wider diameters improve the bone-implant contact within compact bones and thus are preferable. [22][23][24] A study by Bischof et al 25 investigated ITI implants and found that a higher ISQ was seen in the maxilla than in the mandible and in type I than in type III bone; however, stability was not significantly related to site of placement or implant length and diameter. Additionally, up to 4 to 6 weeks after placement, ISQ was maintained or slightly increased, and after 6 weeks, the range of increment became larger.…”
Section: Discussionmentioning
confidence: 96%
“…The mean implant length was 12.2 mm (range, 5-8 mm): 839 short implants [9] were less than 10 mm in length (5.8%), 3,858 implants were between 10 mm and 12 mm length (29.5%), 7,537 implants were between 13 mm and 15 mm length (58.4%), and 913 implants were longer than 15 mm (6.3%). The mean implant diameter was 4.2 mm (range, 3-6 mm): 2,564 narrow-diameter implants [10] were less than 3.75 mm in diameter (19.5%), 8,887 regular-diameter implants were between 3.75 mm and 4.8 mm in diameter (67.6%), and 1,696 were wide-diameter implants with a width of at least 5 mm (12.9%) [11]. …”
Section: Methodsmentioning
confidence: 99%
“…Three studies evaluated only wide-diameter implants. The number of patients evaluated in these studies was as follows: Khayat et al [13] studied 71 patients, Polizzi et al [16] studied 34 patients, and Schincaglia et al [17] studied 15 patients. Schincaglia et al’s study was a randomized controlled trial evaluating immediate-loading versus delay-loading of wide-diameter implants; only data of the control group that was not immediately loaded was included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%